2019
DOI: 10.1039/c8ta11460a
|View full text |Cite
|
Sign up to set email alerts
|

Tailored polymer nanocomposite membranes based on carbon, metal oxide and silicon nanomaterials: a review

Abstract: Research into the structure, synthesis and properties of nanoscale materials has increased at an enormous pace over the past decades since they have a wide variety of applications ranging from adsorption to separation processes in water treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(26 citation statements)
references
References 305 publications
0
26
0
Order By: Relevance
“…The results are reported in terms of FRR, which is a good indication of the membrane fouling recovery after backwashing. 44 The results of the FRR for the modified membranes and pristine PVDF membrane before and after UV exposure are shown in Figure 6. Among all of the membranes, the pristine PVDF membrane showed the lowest FRR because of the hydrophobic nature of the PVDF.…”
Section: Antifouling Propertiesmentioning
confidence: 99%
“…The results are reported in terms of FRR, which is a good indication of the membrane fouling recovery after backwashing. 44 The results of the FRR for the modified membranes and pristine PVDF membrane before and after UV exposure are shown in Figure 6. Among all of the membranes, the pristine PVDF membrane showed the lowest FRR because of the hydrophobic nature of the PVDF.…”
Section: Antifouling Propertiesmentioning
confidence: 99%
“…Hvid et al demonstrated that the UF membranes with hydrophilic surfaces are less exposed to protein fouling and prompted the methods to develop the membrane with the more hydrophilic surface through appropriate modifiers as well as surface coatings 6 . The benefits of incorporation and in‐situ immobilization of nanoadditives to improve the UF membrane performance are also reported 7–9 . On account of desirable film‐forming properties fabrication of CA‐based UF membranes for the purpose of water treatment applications is most widely reported 10–14 .…”
Section: Introductionmentioning
confidence: 99%
“…The development of surface‐modified polymeric UF membranes using nanoadditives has become more popular. These polymer nanocomposite membranes showed excellent stability, permeation, and antifouling ability on account of their synergistic properties due to the interaction of nanoadditives with polymer and the state of dispersion 16–19 . Zhu et al investigated the UF performance of metal oxide nanoparticles such as ZnO, TiO 2 , and Al 2 O 3 incorporated polysulfone UF membrane and found that the TiO 2 nanoparticles incorporated membrane had better hydrophilicity and permeability 20 .…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.1063/1.5119338 Nanoporous media, in particular, monolithic porous membranes, play an increasing scientific and technological role. [1][2][3] Among the applications of porous membranes stand out filtration and separation processes, [4][5][6] the study of confinement effects in soft matter, [7][8][9] and energy harvesting. 10,11 However, their characterization in terms of pore size and pore homogeneity is still an extremely demanding experimental task, even though it is of crucial importance for the interpretation of experiments and for the understanding of functional performance of nanoporous membranes.…”
mentioning
confidence: 99%